2009
DOI: 10.1097/cmr.0b013e32832f159c
|View full text |Cite
|
Sign up to set email alerts
|

Does use of estrogens decrease the Breslow thickness of melanoma of the skin? Oral contraceptives and hormonal replacement therapy

Abstract: Recently, we showed there was a cumulative dose-dependent association between the use of estrogens and the incidence of cutaneous melanoma (CM). This association was shown for both oral contraceptives (OC) and hormonal replacement therapy (HRT). Some in-vitro studies, however, have suggested a direct inhibitory effect on melanoma tumor growth. Therefore, the use of different types of estrogens, OC and HRT, may be associated with a decreased Breslow thickness. Consequently, the clinical impact of our earlier fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…5 Evidence of a role of estrogen in melanoma development and progression has been inconsistent. 6,[35][36][37] Some findings have suggested that the balance of estrogen receptor α to estrogen receptor β may correlate with melanoma progression, 38 but a case series found no sex difference in estrogen receptor β expression in melanocytic nevi or melanomas. 39 In addition, a meta-analysis found no sex difference in the incidence of BRAF and NRAS mutations, which have been associated with cutaneous melanoma development.…”
Section: Discussionmentioning
confidence: 99%
“…5 Evidence of a role of estrogen in melanoma development and progression has been inconsistent. 6,[35][36][37] Some findings have suggested that the balance of estrogen receptor α to estrogen receptor β may correlate with melanoma progression, 38 but a case series found no sex difference in estrogen receptor β expression in melanocytic nevi or melanomas. 39 In addition, a meta-analysis found no sex difference in the incidence of BRAF and NRAS mutations, which have been associated with cutaneous melanoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Records from PALGA were linked to the PHARMO record linkage system (PHARMO RLS). This linkage has been used in previous published studies [18, 19]. Data from the PHARMO RLS consist of multiple observational databases linked on a patient level, covering 3 million inhabitants of geographic defined areas in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…Koomen et al . [ 68 ] showed that there is no such statistically significant association; however, decreased Breslow thickness among women using oestrogen, especially among older women, has not been excluded [ 68 ]. The results of Tang et al .…”
Section: Oestrogen In Melanoma Progressionmentioning
confidence: 99%